THE IMPACT OF FAMILY CONFLICT TOWARD INTENTION TO STAY IN THE FAMILY BUSINESS: THE MODERATING EFFECT OF SOCIOEMOTIONAL WEALTH - Effendi, Laij Victor (Jurnal Aplikasi Manajemen, 2020)
The purpose of this research is to study the impact of family conflict and socioemotional wealth toward the intention to stay in the family business. Furthermore, the study was also to test the moderating effect of socioemotional wealth on the impact of family conflict toward the intention to stay. This research was conducted quantitatively at the individual level. Samples were taken purposively from junior generation working in a family business which is a member of the Indonesia Chamber of Commerce - Surabaya Branch. The data were collected cross-sectionally, and the sum of the proper sample was 96. The data were analyzed with PLS-SEM using SmartPLS3.00. The result of this study shows that family conflict has a negative impact on intention to stay. Socioemotional wealth has a positive impact on the intention to stay. Furthermore, socioemotional wealth has a positive moderating impact on the effect of family conflict toward intention to stay. This study might be useful for a family business owner to consider the development of socioemotional wealth to smooth succession process and to maintain the intention to stay while conflict emerges. The suggestion for further research is to extend to cultural impact at the individual level or personal traits toward intention to stay on the family business.